(untitled) (Journal of Governance and Development (JGD), 2017)
Generally, we have seen successful women that have demonstrated considerable leadership qualities in many areas such as in community and informal organisations, in private and public organisations. However, women have significantly been discriminated through socialisation and negative stereotyping of women and men that reinforce the tendency of decision making positions to remain as the domain of men. In addition, the underrepresentation of women in decision making positions prevents women from having significant impact on many key decisions in organisations. This paper discusses on the participation of women in Joint Consultative Committees (JCC), a form of workers’ representation in public universities in Malaysia. The objective of this paper is to explore the effectiveness of JCC in public universities in Malaysia from women’s perspective. This qualitative study employs in-depth interview technique to analyse the factors contributed to low participation of women in the Academic JCC whilst addressing the importance of women’s participation in public universities environment. The findings have some implication towards the policy making of JCC, hence; it reflects that women’s participation could be beneficial beyond the traditional JCC practices for the public universities in Malaysia.